Analisis Pengaruh Word of Mouth dan Brand Image Terhadap Keputusan Pembelian pada Waroeng Spesial Sambal "SS" Jember - Mochammad Fariz Pradana; Mohamad Dimyati; Ari Subagyo (Jurnal Ekonomi Akuntansi dan Manajemen, 2019)
The research aims to analyze influence of work discipline, Work Environment and Work Stress variables to employee performance Akademi Kebidanan Dr. Soebandi Jember. Data is used in this study was primary data obtained from a questionnaire that was given to the respondent. The sampling method used in this study was issaturated with a total sample of 44 respondents. Data analysis method used is multiple linear regression analysis method.The results of this study indicate that discipline significant positive operating environment performance employees Akademi Kebidanan Dr. Soebandi Jember, physical sgnificant positive operating environment performance employees Akademi Kebidanan Dr. Soebandi Jember. Workplace non physical significant positive operating environment performance employees Akademi Kebidanan Dr. Soebandi Jember. Job stress influential significant positive operating environment performance employees Akademi Kebidanan Dr. Soebandi Jember. Keywords: Work Discipline, Employee Performance, Work Environment, Work Stress